1981
DOI: 10.1007/bf01721260
|View full text |Cite
|
Sign up to set email alerts
|

The “glucose effect” in acute hepatic porphyrias and in experimental porphyria

Abstract: The "glucose effect" was investigated in human acute hepatic porphyrias (acute intermittent porphyria, variegate porphyria, coproporphyria and porphobilinogen synthase defect porphyria) and in avian liver cells. 8 patients (7 women) with acute abdominal-neurological porphyria syndrome and 3 patients (2 women) in the remission phase were treated with high carbohydrate intake (approximately 500 g/24 h), mainly in form of intravenous glucose infusions. The biochemical response with a decrease of metabolites of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…The extreme increase of porphyrin precursor excretion in acute intermittent porphyria, variegate and coproporphyria (13) can only be explained on the basis of the secondarily limiting f riction of uroporphyrinogen synthase (15 -18). Meanwhile the rate limiting function of uroporphyrinogen synthase for the conversion of ALA into protoporphyrin was proven in homogenates (19) and the "glucose effect" was demonstrated in liver cell cultures (11,(20)(21)(22). In the present study 1. the "glucose effect" on porphyrin synthesis is compared in vitro and in vivo and 2. the intriguing role of uroporphyrinogen synthase s a secondary limiting factor is considered in view of the glucose-mediated repression of counterregulation in acute hepatic porphyrias.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…The extreme increase of porphyrin precursor excretion in acute intermittent porphyria, variegate and coproporphyria (13) can only be explained on the basis of the secondarily limiting f riction of uroporphyrinogen synthase (15 -18). Meanwhile the rate limiting function of uroporphyrinogen synthase for the conversion of ALA into protoporphyrin was proven in homogenates (19) and the "glucose effect" was demonstrated in liver cell cultures (11,(20)(21)(22). In the present study 1. the "glucose effect" on porphyrin synthesis is compared in vitro and in vivo and 2. the intriguing role of uroporphyrinogen synthase s a secondary limiting factor is considered in view of the glucose-mediated repression of counterregulation in acute hepatic porphyrias.…”
Section: Introductionsupporting
confidence: 48%
“…Porphyria precipitated by fasting (8), porphyrinuria induced by fasting in nonporphyric subjects (9) and "caloripenic porphyria" (10) were next reported and i t was suggested that a low-caloric diet or abrupt reduction in carbohydrate and protein intake may provoke Symptoms in addition'to elevating urinary ALA, pyrrol and porphyrin excretion (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate intake blocks ALA‐synthase, which has been demonstrated in numerous clinical and experimental studies [ 4–8]. However, the mechanisms by which carbohydrates modulate the components of porphyrins and haeme synthesis are highly complex and only partially elucidated to date [ 5].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate intake blocks ALA‐synthase, which has been demonstrated in numerous clinical and experimental studies [ 4–8]. However, the mechanisms by which carbohydrates modulate the components of porphyrins and haeme synthesis are highly complex and only partially elucidated to date [ 5]. Treatment of AIP patients entails treating both the symptoms and the complications, but also requires an endeavour to reverse the fundamental disease process by a carbohydrate‐rich diet and by treating the attacks with intravenous infusions of glucose or haeme.…”
Section: Introductionmentioning
confidence: 99%
“…Though 50% of acute attacks in patients with VP may settle spontaneously, withholding the drug is always potentially risky as the onset of neuropathy is impossible to predict and is usually rapid in onset. 155 Carbohydrate loading has been shown to inhibit porphyrin synthesis 221,235,236 and glucose infusion was previously recommended as part of the management of the acute attack. The anti-porphyrogenic effect of glucose is, however, insignificant in comparison with the effect of heme replacement; where the latter is available, there is no need for glucose infusion, particularly since infusion of hypotonic fluids may aggravate hyponatraemia.…”
Section: E Treatment Of the Acute Attackmentioning
confidence: 99%